Hepato-Renal Crosstalk in Acute and Chronic Disease: From Shared Pathways to Therapeutic Targets - Anna Clementi; Grazia Maria Virzì; Massimiliano Sorbello; Nenzi Marzano; Paola Monciino; Jose Said Cabrera-Aguilar; Giovanni Giorgio Battaglia; Claudio Ronco; Monica Zanella (Biomedicines)
Hepato-renal crosstalk is a complex biological communication between liver and kidneys mediated by various factors, including cellular, endocrine, and paracrine molecules. This interaction highlights the functional consequences that damage in one organ can have on the other. In particular, the liver and kidney play a pivotal role in maintaining body homeostasis, as they are both involved in the excretion of toxic bioproducts and drugs. The overlap of liver and kidney disease has both therapeutic and prognostic implications. Therefore, a better understanding of the mechanisms involved in the pathogenesis of this bidirectional crosstalk is essential for improving the management of these clinical conditions and patient outcomes. Specifically, a multidisciplinary approach involving hepatologists and nephrologists is crucial to reduce the long-term burden of these clinical settings. This review focuses on the hepato-renal crosstalk in the context of liver and kidney disease, with particular attention to acute kidney injury associated with liver injury, hepatorenal syndrome and, chronic kidney disease in the context of liver fibrosis.